An Empirical Study and a Framework for Effective Risk Management in Scrum: Effective Risk Management in Scrum - Ali, Muneeb; Hafeez, Yasir; Hamid, Bushra (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
Now a day, agile methods are broadly used for software development. The agile methods are expected to provide virtuous outcomes and producing better quality software products that achieves the customer requirements. In view of the contemporary scenario, it is clear that secure and better quality software products are foremost apprehension. This research study deals with risk management within the scrum framework. The purpose of this research was to propose and validated a framework developed that produces quality product. The continuous approach of scrum overlooks the risk issues which can result in changes and cost expansion. To mitigate this risk, a free scrum model is proposed. This model is produced by combining the activities of risk management and in scrum methodology. A case study has been employed to evaluate proposed framework for mitigating risks effectively in scrum process. We used a qualitative approach with structured interviews, to validate the proposed work. We have explored both the existing principle theory for risk management and the results of different empirical studies to build the framework. On the said base, we have drawn up vindicated proposals for the framework. Results of case study has shown that the proposed framework is suitable for the developing a quality software product. By employing the risk management activities into scrum methodology, as per proposed framework, there is a promising scrum model to control risk. This also ensures software quality along with benefits of cost reduction, experience gained and customer satisfaction. This framework has implications with the effective risk management in scrum way of development and provide valuable insights for risk management scrum. The case study provides direction for future research and lesson learned. It will also provide assistance to apply effective principles of risk management in scrum to develop high quality software product. Our future research will be directed toward the generalization of this framework. The proposed framework activities will be applied on different agile methodologies and other case studies will be conducted, so the results can be generalized.